DEIXIS INVESTIGATION IN SHAKIRA ISABEL’S SPEECH ABOUT EDUCATION CHANGES THE WORLD - Azzahra, Heldina (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2023)
The research aims to investigate the types of deixis used by Shakira Isabel in her speaking for global quality education at the WISE conference in Qatar. This research is based on the theory that reveals by Levinson (1983). This study has differences from previous research in terms of data analysis theory. In previous studies, researchers used theories from Yule (2014), Yule (1996), and C.S Peirce, while this study used theory from Levinson (1983). The object of this research is the speech transcript of Shakira Isabel. The researcher applied descriptive qualitative research. This study was classified as documentary research since the data was taken from a document or written text that is a speech transcript. The research showed 139 data with 96 (69%) person deixis, 2 (1%) place deixis, 10 (7%) time deixis, 17 (12%) social deixis, and 14 (10%) discourse deixis. Therefore, it can be said that Shakira Isabel’s speech at the WISE conference in Qatar tends to use the person deixis as the dominant type of the other types.